Vaginal Touch versus Transvaginal Ultrasound in the Management of Threatened Preterm Labour at the University Hospital Center of Porto-Novo (Benin) - OGOUDJOBI, OGOURINDÉ MATHIEU; TSHABU TSHINGUTA ÉPSE AGUEMON, CHRISTIANE; LOKOSSOU, Mègnissè Sèna H. S.; TOGNIFODE, Véronique; ABOUBAKAR, MOUFALILOU; KOMONGUI, DIDIER GOUNOU; TONATO BAGNAN, Josiane Angeline; LOKOSSOU, ANTOINE; TAKPARA, ISSIFOU; PERRIN, RENÉ-XAVIER (My University, 2017)
Objective: To evaluate the risk of preterm delivery with vaginal touch in opposition with transvaginal ultrasound in pregnant women who present signs and symptoms of threatened preterm labour. Methods: A prospective study was conducted with descriptive and comparative aims at the University Hospital of Porto-Novo, Benin Republic between 1 March and 31 August 2016. Every pregnant woman admitted to the emergencies of the maternity between 28 and 34 of WA (weeks of amenorrhoea) and attended for preterm delivery risk with intact membranes was included. The risk of preterm delivery was evaluated using vaginal touch and ultrasound examination of cervical length. Results: The risk of preterm delivery was obvious and identical with the cervical dilatation ≥2 cm when the vaginal touch was applied [RR 2.34 IC 95% (1.71 - 3.20)] and ultrasound examination of cervical length <25 mm [RR 2.44 IC 95% (1.43 - 4.16)]. The cervix obliteration was not statistically linked to preterm delivery. The ultrasound examination of cervical length had a better sensitivity (87.76%) and a negative predictive value (81.54%) against 59.18% and 74.68% respectively for cervical dilatation at vaginal touch. Bishop score also had a better specificity with the one of the ultrasound examination of cervical length (79.11% vs. 33.54%) whereas both of them had almost identical negative predictive value (81.17% vs. 81.54%). Conclusion: Vaginal touch was also as relevant as transvaginal ultrasound while evaluating the risk of preterm delivery. For the lack of ultrasound in emergency rooms, a good physical examination would be sufficient by its own to decide of an adequate management when there is a threat of preterm delivery.
Keywords: Threat of Preterm Delivery; Vaginal Touch; Transvaginal Ultrasound; Comparison